Is sleep length predicted by our personality? - Butković, Ana; Bratko, Denis (2012)
Research has shown that sleep length predicts morbidity and mortality for both short and long sleepers. Therefore, it has been of interest to determine all that influences the duration of sleep, with personality as one of the candidates. This study explores the relationship between five-factor model of personality and sleep length. Data was collected on 651 twins (M = 18.62, SD = 2.31) as part of a larger project. Significant negative correlations were found with neuroticism and openness. Hierarchical regression analysis was run with sex and age entered first and personality dimensions second. Sleep length was explained with personality dimensions of neuroticism and openness. Finally, when our participants were divided into short, moderate and long sleepers, we found that short sleepers had significantly higher neuroticism score than both moderate and long sleepers and higher openness scores than long sleepers.
Projekt MZOS
ENG